Produção e caracterização de quimeras recombinantes C e D de Clostridium botulinum - Gil, Luciana Aquini Fernandes (2012)
Bovine Botulism is a lethal intoxication caused by the ingestion of the neurotoxins produced by Clostridium botulinum types C and D that inhibit the release of acetylcholine at the neuromuscular junction leading to death by flaccid paralysis. It produces important economic losses, being a major cause of casualties in cattle in several regions of Brazil. The control of the disease depends on the presence of neutralizing antibodies against botulinum neurotoxins (BONTs) in immunized cattle. Immunization is obtained inoculating toxoids produced from cultures of selected strains of C. botulinum types C and D, whose industrial production has limitations concerning efficiency and productivity. An alternative to the use of these toxoids is the production of recombinant antigens with high levels of purity and antigenicity. The C-terminal fraction of the heavy chain of botulinum neurotoxins has been the main target in the development of recombinant vaccines with promising results. In this work, two recombinant bivalent chimeras for the control of bovine botulism consisting of the neuronal receptor binding domains (NRBDs) of botulinum C and D toxins were efficiently produced in Escherichia coli. They were characterized and evaluated in mice, with promising results. Both the recombinant chimeras rLTB-C-D and rC-D were produced by cloning and expressing a synthetic gene encoding the C-terminal portion of both BONTs. The former also included the preferred codons of the E. coli heat labile enterotoxin B subunit (LTB), a potent humoral immune adjuvant. The levels of expression of the recombinant antigens were satisfactory, yielding approximately 100 mg of each recombinant antigen per liter of culture. An ELISA performed to assess the antigenicity of the molecules showed that both were recognized by sera of immunized mice suggesting the preservation of epitopes with the properties of native BONTs. Both chimeras induced high levels of neutralizing antibodies without undesirable effects. The level of neutralizing antibodies of the groups inoculated with equimolar concentrations of rLTB-C-D and rC-D containing Aluminum Hydroxide as adjuvant were similar, confirming the adjuvant properties of LTB. These results demonstrated that the recombinant chimeras were immunogenic. Sera from mice inoculated with commercial vaccines were also analyzed by ELISA using as antigens rC and rD, corroborating the neutralization.